Improving Learning Motivation through Fun Games in Children at SB Permai Penang Malaysia - Adelia Kurnia Putri; Alfina Dian Arista; Dwi Wulan Sari; Osfir Candikia Rara Komara; Sugeng Riyanto (Asosiasi Lembaga Pendidikan Tenaga Kependidikan Peguruan Tinggi Muhammadiyah dan Aisyiyah, 2023)
One of the challenges faced by the future generation of Indonesia is the equalization of education, especially for the children of migrant workers residing in Malaysia. These children often experience educational disparities due to a lack of access and learning facilities. To address this issue, the Indonesian community in Malaysia has collaborated with the Indonesian Embassy and Consulate in providing educational services for the children of migrant workers. However, these efforts have not been sufficient to foster a sense of learning enthusiasm among these children. Therefore, we, as students participating in the KKN-Dik program, have initiated a community service program aimed at enhancing the motivation to learn in children through fun games. This program uses a participatory method that actively involves educators and students in the learning process. Consequently, we hope to ignite the interest and motivation of children in learning and provide them with an enjoyable and meaningful learning experience at SB Permai Penang, Malaysia.